As medidas cautelares diversas da prisão: o uso da ferramenta no contexto da pandemia de COVID-19 - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This paper aims to present the precautionary measures other than imprisonment estabilished in the Brazilian legislation as a way to assist in reducing the over imprisonment phenomenom during the global pandemic of Covid-19. To reach this goal, a descriptive qualitative research was used, through an extensive documental and bibliographic analysis of books, articles, legislations, doctrines, vídeos and technical reports released about the effects of the global pandemic in Brazil, especially regarding Brazilian prisons. To enable a more in-depth analysis, this paper sought to reflect on the facets and characteristics of the Punitive State estabilished in Brazil, specifically its connection to the criminalization of the poor and how this phenomenom affects the current problem of over imprisonment in Brazil. Once this cenárioo was estabilished, we sought to delve into the reasons behind the creation of the precautionary measures that were added into the Code of Criminal Procedure in 2011, as well as the benefits brought by them, especially considering their use in the contexto of the Covid-19 pandemic. Therefore, the need to apply such measures was emphasized in order to ensure the reduction in the number of people overcrowding prisons, consequently reducing the risks of infection according to the prevention measures estabilished by WHO. Finally, the inefficiency of the use of precautionary measures by the legal system during the global pandemic of Covid-19 was observed, explicitly demonstrating the need for changes regarding the application of such measures, and also regarding the idea imbued in Society that the only formo f punishment is imprisonment.
The various precautionary measures of prison: the use of the tool in the context of the COVID-19 pandemic
Keywords: Medidas cautelares; Prisão; Estado punitivo; Pandemia; Precautionary measures; Imprisonment; Punitive state; Pandemic; CNPQ::CIENCIAS SOCIAIS APLICADAS